GAMBARAN KADAR KOLESTEROL LOW DENSITY LIPOPROTEIN (LDL) PADA PEROKOK AKTIF DI BANJAR TAMAN DESA DARMASABA KECAMATAN ABIANSEMAL BADUNG - Cok Dewi Widhya Hana Sundari (Meditory : The Journal of Medical Laboratory, 2018)
Low Density Lipoprotein (LDL) cholesterol is a lipoprotein compound that has low-density. Smoking activity can increase LDL cholesterol levels. The nicotine compound in cigarettes can increase the oxidation of LDL cholesterol that will cause atherosclerosis. This research used descriptive study. The purposed of this study was to known about the level of LDL cholesterol in active smoker serum at areas Banjar Taman, Darmasaba Village, Abiansemal, Badung. Sampels in this research are males active smoker aged 18 years old and over which amount to 30 sampels. That sampling using accidental sampling. Examination of LDL cholesterol using Calculated method. The result of LDL concentration on this research based on the characteristics of the respondens such as: normal concentration of LDL on the group of 18-40 years (60%), with time period of smoked less than 5 years (53.4%) and the light smokers category (36 , 7%). Concentration of LDL exceeded the normal limits found on the group of 18-40 years (23.3%), smoked with 6 until 10 years period have 16.7% and category of light smokers (26.7 %). The conclusion of this research , were: 66.7% have normal levels and 33.3% with over normal limits. Active smokers were expected to reduce or stop smoked habits for the better health quality.